Mathematical Modeling of Operational Reliability of Mine Lifting Equipment Based on Censored Data; Mathematics; Vol. 14, iss. 4 - Zadkov D. A. Denis Aleksandrovich; Martyushev N. V. Nikita Vladimirovich; Malozemov B. V. Boris Vitaljevich; Demin A. Yu. Anton Yurievich; Pogrebnoy A. V. Aleksandr Vladimirovich; Kuleshova E. E. Elizaveta Evgenjevna; Valuev D. V. Denis Viktorovich (2026, 2026)
Title screen